Analysis Risk K3 Using JSA and HIRARC Methods Phosphoric Acid Factory on PT. Petrokimia Gresik - Rozikin, Muhammad Khoiru; Hidayat, Hidayat; Rizqi, Akhmad Wasiur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
PT. Petrokimia Gresik is one of the industries that produce fertilisers, non-fertilizers, and other chemicals. PT. Petrokimia Gresik is divided into several departments, including the phosphoric acid factory. This research aims to identify and reduce potential hazards during the production process. This research uses (JSA) method to identify the hazard stage and (HIRARC) method to conduct risk analysis. Based on the risk hazard identification results, each job will be assessed based on severity and likelihood to establish the risk level. The research found that all extreme-risk jobs had 4 risks, high risks had 15 risks, medium risks had 2 risks, and no jobs with low-risk levels were found. The control plan carried out in this study is to control by elimination, engineering, administration, and personal protective equipment (PPE). Keywords: Occupational Health Safety, JSA, HIRARC.